2015
DOI: 10.1016/j.renene.2015.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fermentative H2 production by hydrolysis byproducts of lignocellulosic substrates

Abstract: a b s t r a c tLignocellulosic materials are potential renewable substrates for fermentative H 2 production; however, most of the methods available to hydrolyze these materials produce fermentation inhibitors. This study assessed the effect of three different groups of inhibitors on fermentative H 2 production by a mixed culture: (1) acetic acid; (2) furan derivatives, such as furfural and 5-hydroxymethylfurfural (HMF); and (3) phenolic monomers, such as vanillin, syringaldehyde, and 4-hydroxybenzoic acid (HBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 33 publications
4
19
1
2
Order By: Relevance
“…As previously reported, at T MAX ¼ 206 C, high percentages of hemicellulose were removed but also primary degradation products (F and HMF) were kept at relatively low levels, which could be achieved by applying pretreatment conditions of moderate severity. Although pretreatment improves enzymatic access to cellulose for further fermentation, it generates byproducts decomposition which may affect negatively fermentation [35].…”
Section: Composition Of Liquid Phase Resulting From Autohydrolysis Prmentioning
confidence: 99%
“…As previously reported, at T MAX ¼ 206 C, high percentages of hemicellulose were removed but also primary degradation products (F and HMF) were kept at relatively low levels, which could be achieved by applying pretreatment conditions of moderate severity. Although pretreatment improves enzymatic access to cellulose for further fermentation, it generates byproducts decomposition which may affect negatively fermentation [35].…”
Section: Composition Of Liquid Phase Resulting From Autohydrolysis Prmentioning
confidence: 99%
“…These inhibitors negatively affect the cell membrane function, growth and glycolysis of fermentative bacteria (Behera et al, 2014). Several studies investigated the inhibitory effects of fermentative inhibitors on biohydrogen fermentation (Cao et al, 2010;Kongjan et al, 2010;Liu et al, 2014;Park et al, 2011;Quéméneur et al, 2012;Siqueira and Reginatto, 2015). Cao et al demonstrated the inhibition effect of furfural, 5-HMF and phenolic compounds from acid-pretreated cornstalk on thermophilic hydrogen fermentation by using Thermoanaerobacterium thermosaccharolyticum W16 (Cao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed all the samples treated in this study, to detect HMF at 0.1, 0.5, 1.1, 1.9, 2.8, and 7.6 mg/L after autoclave treatment of the sample for 1, 2, 3, 4, 5, and 6 h, respectively. Such concentrations were very low as compared to fermentation inhibitory concentrations described for H 2producing Clostridium in the literature: above 1.0 g/L [18,30,31].…”
Section: Macroalgae Hydrolysate Chemical Characterizationmentioning
confidence: 58%
“…Apart from different carbohydrate types, algae biomass hydrolysates may contain significant levels of non-sugar components, such as 5-HMF, a product of hexose degradation that is toxic to microbes used to convert biomass to biofuels [18,30,31]. Therefore, it is desirable that hydrolysates contain fermentable sugars but low inhibitor concentration.…”
Section: Macroalgae Hydrolysate Chemical Characterizationmentioning
confidence: 99%